A 'click' chemistry approach to novel entinostat (MS-275) based class I histone deacetylase proteolysis targeting chimeras. Issue 12 (1st November 2022) - Cross, Jasmine M.; Coulson, Megan E.; Smalley, Joshua P.; Pytel, Wiktoria A.; Ismail, Ozair; Trory, Justin S.; Cowley, Shaun M.; Hodgkinson, James T.
Abstract : Click chemistry was utilised to prepare a library of PROTACs based on entinostat a class I histone deacetylase (HDAC) inhibitor in clinical trials. Abstract : Click chemistry was utilised to prepare a library of PROTACs based on entinostat a class I histone deacetylase (HDAC) inhibitor in clinical trials. A novel PROTAC JMC-137 was identified as a HDAC1/2 and HDAC3 degrader in HCT116 cells. However, potency was compromised compared to previously identified class I HDAC PROTACs highlighting the importance in the choice of HDAC ligand, functional group for linker attachment and positioning in PROTAC design.